2017
DOI: 10.1186/s12936-016-1655-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a fixed-dose combination of artesunate and amodiaquine for the treatment of uncomplicated Plasmodium falciparum malaria in real-life conditions of use in Côte d’Ivoire

Abstract: BackgroundIn many malaria-endemic, sub-Saharan African countries, existing pharmacovigilance systems are not sufficiently operational to document reliably the safety profile of anti-malarial drugs. This study describes the implantation of a community-based pharmacovigilance system in Côte d’Ivoire and its use to document the safety of ASAQ Winthrop® (artesunate–amodiaquine).MethodsThis prospective, longitudinal, descriptive, non-comparative, non-interventional study on the use of artesunate–amodiaquine in real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Patients diagnosed with uncomplicated malaria who reported adverse events had almost three times the odds of interrupting treatment than those who did not (holding age and region constant). The most common side effects of fatigue, drowsiness and nausea/vomiting associated with ASAQ were consistent with studies evaluating the safety of ASAQ [1618]. Even if the adverse events were minor, it is important that prescribers consider potential adverse events when educating patients upon prescribing ACT.…”
Section: Discussionsupporting
confidence: 72%
“…Patients diagnosed with uncomplicated malaria who reported adverse events had almost three times the odds of interrupting treatment than those who did not (holding age and region constant). The most common side effects of fatigue, drowsiness and nausea/vomiting associated with ASAQ were consistent with studies evaluating the safety of ASAQ [1618]. Even if the adverse events were minor, it is important that prescribers consider potential adverse events when educating patients upon prescribing ACT.…”
Section: Discussionsupporting
confidence: 72%
“…There are also ongoing initiatives with DP combinations to improve their packaging to facilitate correct use to further improve their overall effectiveness and value, with published studies showing a single course treatment for uncomplicated falciparum malaria is well tolerated [269,270]. Assi et al (2017) have also demonstrated that the artesunate-amodiaquine FDC is well tolerated to treat uncomplicated PCP malaria under real-life conditions [271], with this combination now widely used. Banek et al (2018) have shown that co-formulated artemether-lumefantrine (AL) and fixed dose amodiaquine-artesunate (AQAS) have high self-reported adherence rates among children [272].…”
Section: Malaria Including Preventionmentioning
confidence: 99%
“…Life-threatening neutropenia [ 4 ] and hepatitis [ 5 ] stopped the use of amodiaquine in continuous antimalarial chemoprophylaxis, but there have not been significant adverse effects reported in intermittent prophylaxis. Other serious adverse reactions [ 6 ] such as extrapyramidal movement disorders [ 7 , 8 ] are rare [ 9 ] following standard regimens for treatment and use in SMC. By contrast, asthenia and asthenia-like reactions have been reported frequently (9% to 36.6%) and have a higher incidence with ASAQ than with other ACTs [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other serious adverse reactions [ 6 ] such as extrapyramidal movement disorders [ 7 , 8 ] are rare [ 9 ] following standard regimens for treatment and use in SMC. By contrast, asthenia and asthenia-like reactions have been reported frequently (9% to 36.6%) and have a higher incidence with ASAQ than with other ACTs [ 8 , 10 , 11 ]. Metabolism of amodiaquine to toxic reactive quinoneimine intermediates [ 12 ] may contribute towards development of neutropenia, but the physiological mechanisms underlying its more common adverse drug reactions are not well understood.…”
Section: Introductionmentioning
confidence: 99%